2020
DOI: 10.3389/fnhum.2020.00364
|View full text |Cite
|
Sign up to set email alerts
|

Altered Topological Properties of Brain Structural Covariance Networks in Patients With Cervical Spondylotic Myelopathy

Abstract: Background: Brain structural alterations play an important role in patients with cervical spondylotic myelopathy (CSM). However, while there have been studies on regional brain structural alterations, only few studies have focused on the topological organization of the brain structural covariance network. This work aimed to describe the structural covariance network architecture alterations that are possibly linked to cortex reorganization in patients with CSM. Methods: High-resolution anatomical images of 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 69 publications
2
10
0
1
Order By: Relevance
“…The lower Lp, λ, and Cp, and higher Eglob indicated a decrease in local specialization and increased global integration in CSM patients. This suggests a shift towards a randomized network in functional brain networks, which is consistent with the results of a recent study focusing on topological properties alteration of brain structural covariance networks in CSM patients (25). This randomization in networks has also been reported in AD, social anxiety disorder (SAD), and MDD (22,35).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The lower Lp, λ, and Cp, and higher Eglob indicated a decrease in local specialization and increased global integration in CSM patients. This suggests a shift towards a randomized network in functional brain networks, which is consistent with the results of a recent study focusing on topological properties alteration of brain structural covariance networks in CSM patients (25). This randomization in networks has also been reported in AD, social anxiety disorder (SAD), and MDD (22,35).…”
Section: Discussionsupporting
confidence: 89%
“…Previous neuroimaging CSM studies have found a correlation between disease symptoms and functional connectivity in specific resting-state brain regions or networks and indicated the human brain connectome as an underlying biomarker of CSM (16,24). A recent study based on topological characteristics of the structural network in CSM patients found a lower Cp and shorter characteristic path length (Lp) in the brain structural covariance network (25). More specifically, that study indicated a shifting brain structural network trended towards random brain networks and found increased betweenness in sensorimotor-related brain areas, which may support the cortex reorganization theory involved in the recovery of sensory-motor function in CSM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Injury to the cervical spinal cord causes structural and functional connectivity changes within the brainstem and cerebrum that may include adaptive neuroplasticity. 90 , 194 , 195 Studies in DCM, principally using advanced MRI techniques, 196 - 202 but also transcranial magnetic stimulation, 203 have demonstrated that the presence and nature of these changes can represent clinical symptoms, including pain and neuromuscular function, and predict response to surgery. Principal regions of interest have been the visual pathways (hypothesized to represent an increase reliance on vision for balance) 201 , 204 and supplementary motor areas.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate the functional impairments result from the structural damage in sensorimotor cortices in CSM patients. Converging evidence shows that CSM patients have little gray matter (71)(72)(73) and low metabolism in the sensorimotor cortices (14,74). Therefore, the structural changes may result from the FCS changes in the precentral and postcentral gyrus.…”
Section: Discussionmentioning
confidence: 99%